Hemophilia in the south of Tunisia. Issue 7 (22nd October 2022) - Kassar, Olfa; Charfi, Maha; Megdiche, Fatma; Fakhfakh, Yosra; Kallel, Faten; Hdijji, Sondes; Elloumi, Moez
Abstract : Hemophilia is a rare constitutional hemorrhagic disorder. There is insufficient epidemiological data on hemophilia in Tunisia. To describe the epidemiological, clinical, therapeutic, and outcome of a cohort of patients with hemophilia in southern Tunisia. A retrospective study was conducted on patients with hemophilia at the Hemophilia Treatment Center of Southern Tunisia in Sfax over 38 years (from January 1982 to December 2020). Data were collected in a regional hemophilia registry of the South Tunisian center. We collected 141 cases of hemophilia, 85% of whom had hemophilia A and 15% had hemophilia B. The severe form represented 65%, followed by the moderate form at 25%. The prevalence of hemophilia was 4.4 in 100 000 population. Family history of hemophilia was found in 70%. The mean age of patients at diagnosis was 28 months. Hemophilia was detected in 87% of cases after hemorrhagic syndrome. Bleeding occurred mainly in hemarthrosis (73%), hematoma (70%), and visceral bleeding (28%). Intracranial bleeding occurred in 6% of cases. Thirty-six percent of patients were on prophylactic therapy. Hemophilic arthropathy was the most important orthopedic complication in our patients (38%). Inhibitory antibodies occurred in 16% of PWH. Transfusion-transmitted infections with HIV and hepatitis C were in 2 and 31% of cases, respectively. The prevalence of hemophilia is still underestimated in our center. The severe form of hemophilia is the most frequent. Hemophilic arthropathy was the most important complication in our patients. This showed that hemophilia is still a disabling disease in our country.